Molecular alterations in bone marrow mesenchymal stromal cells derived from acute myeloid leukemia patients - Heide, Eva Kristin von der; Nowak, Daniel; Hofmann, Wolf-Karsten (Leukemia, 2017)
The contribution of molecular alterations in bone marrow mesenchymal stromal cells (BM-MSC) to the pathogenesis of acute myeloid leukemia (AML) is poorly understood. Thus we assessed genome-wide genetic, transcriptional and epigenetic alterations in BM-MSC derived from AML patients (AML BM-MSC). Whole-exome sequencing (WES) of AML BM-MSC samples from 21 patients revealed a non-specific pattern of genetic alterations in the stromal compartment. The only mutation present in AML BM-MSC at serial time points of diagnosis, complete remission and relapse was a mutation in the PLEC gene encoding for cytoskeleton key player Plectin in one AML patient. Healthy donor controls did not carry genetic alterations as determined by WES. Transcriptional profiling using RNA sequencing revealed deregulation of proteoglycans and adhesion molecules as well as cytokines in AML BM-MSC. Moreover, KEGG pathway enrichment analysis unravelled deregulated metabolic pathways and endocytosis in both transcriptional and DNA methylation signatures in AML BM-MSC. Taken together, we report molecular alterations in AML BM-MSC suggesting global changes in the AML BM microenvironment. Extended investigations of these altered niche components may contribute to the design of niche-directed therapies in AML.